Elmore Leonard's Bandits. - Leonard, Elmore, 1925-2013 (Arbor House, 1987)
Bandits assembles an unlikely crew: an ex-cop, an ex-con, and an ex-nun. They've got their eyes on several million bucks intended for the Contras; with their unique set of skills and their crazily clever plan, they're sure to make out like bandits -- if they live so long.